Organizational challenges in (Model-Based) Requirements Engineering in the automotive industry - Hakala, Tommi (2019)
The development of modern technologies has led to major changes in the automotive industry. Requirements Engineering has become pivotal for the success of development projects. The way how organisations operate within a company or between several companies is one of the most important aspects of Requirements Engineering. This research study represents an extension of the earlier research studies in a way that it deepens and broadens the understanding of organizational challenges in the automotive industry. This paper addresses organizational challenges that occur in the automotive companies on a daily basis. The aim of the research study is to understand what kind of challenges exist when it comes to the Requirements Engineering practices. The study also aims to propose suitable solutions to improve the companies’ operations based on the empirical evidence. Literature review is used as an approach for the theoretical part and this is used as a basis for the research study. The qualitative data was gathered from the companies using semi-structured interviews (n=22). The collected data was studied utilizing the thematical data analyzing method. The findings identify multiple challenges and improvement proposals which have been divided into three themes: Communication & Co-Operation, Organizational Culture and People Skills. Requirements Engineering practices in the automotive companies can be developed further when these challenges and proposed improvements are carefully studied and understood.